Implementation of ecotourism concept in Jambi Province - Hidayat, Angger; Anggriani, Latusi; Siregar, Fitri Ana; Yulistian, Saldi; Jumriatunnisah, Nur (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
Ecotourism has a close relationship with sustainable tourism management, making ecotourism development strategies highly suitable for preserving ecosystems and playing a vital role in the conservation and management of natural habitats for species while creating economic benefits for local communities. Being a province with the highest number of national parks poses a unique challenge for Jambi Province as a pioneering province in ecotourism concept development. This research is crucial as it requires an in-depth examination of the limitations and challenges faced during the development process in order to establish Jambi Province as a model province for ecotourism. Qualitative analysis through literature review is essential to determine the extent to which the implementation of the ecotourism concept is applied in Jambi Province. The objective is to identify the limitations and challenges in the ecotourism development process in Jambi. The expected benefits of this research include expanding knowledge on limitations and challenges in ecotourism development and providing input for the future development of national parks tourism in Jambi Province. The results of this study indicate that the main aspect of ecotourism, conservation principles, is well implemented in Jambi Province, although challenges remain in the social and economic aspects. Some of the limitations in implementing social and economic principles include (a) the need for community involvement as stakeholders in planning, implementation, and monitoring of ecotourism development to enhance cohesion among individuals in the community; (b) collaboration between the government, non-governmental organizations, and entrepreneurs that still have room for optimization to ensure equitable and fair distribution of tourism benefits; (c) ecotourism, seen as a comprehensive product of natural attractions, has been established, but it is yet to be supported by tourism activities focused on nature and environmental conservation efforts.